Micro-Raman spectroscopy and SEM/EDX applied to improve the zircon fission track method used for dating geological formations - Coelho Dias, Airton Natanael [UNESP]; Tello Saenz, Carlos Alberto [UNESP]; Leopoldo Constantino, Carlos Jose [UNESP]; Soares, Cleber Jose [UNESP]; Novaes, Felipe Ponciano [UNESP]; Osorio Araya Balan, Ana Maria [UNESP] (John Wiley & Sons Ltd, 2009)
The zircon mineral is widely studied in geochronology. In the case of the fission track method (FTM), the age is determined by the density of fission tracks at the zircon surface, which can be observed with an optical microscope after an appropriate chemical treatment (etching). The etching must be isotropic at the zircon grain surface to be used in the FTM, which leads those zircon grains whose etching is anisotropic to be discarded. The only reason for this discarding is the nonuniform morphology of the surface grain seen by optical microscopy, that is, no further physicochemical analysis is performed. In this work, combining micro-Raman and scanning electron microscopy (SEM) to study the etching anisotropy, it was shown that zircon grains that present at least one area at the surface where the density of fission track is uniform can be used in the FTM. The micro-Raman showed characteristic spectra of the standard zircon sample either from the areas where there are tracks or from where there are not. The only difference found was in the Raman bandwidths, which were broader for the areas with higher density of fission tracks. This suggests simply a decrease in the relative percentage of the crystalline/amorphous phases at these areas. The SEM/energy dispersive spectrometry (EDX) showed that there were no significant differences in the principal chemical composition at the areas with and without fission tracks. Copyright (c) 2008 John Wiley & Sons, Ltd.
Keywords: Micro-Raman spectroscopy; SEM/EDX; zircon; etching anisotropy; fission track method